Introduction: Workshop objectives and expected outputs - Lebbie, S.H.B. (Southern African Development Community, 2001)
This paper first presents an introduction about the workshop, which includes background and aims. It then outlines the relevance of the workshop to the realization of the SACCAR mandate and objectives; and summarises the objectives and the expected outputs of the workshop. It ends with the workshop procedure.